SUSTAINABLE MANUFACTURING PRACTICES IN A MALAYSIAN AUTOMOTIVE COMPANY: A PERSPECTIVE FROM HOFSTEDE’S CULTURAL MODEL - Syed Mohamed, M.S.; Saptari, A.; Nor Ma’arof, M.I. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
Industrial practices are moving towards an environmentally sustainable manufacturing philosophy. Depending on local environmental requirements companies have adopted practices with different priorities and different intensity. A survey was conducted with the aims to identify the awareness level of sustainable manufacturing practices and to analyze problems faced in implementing sustainable manufacturing from the perspective of Hofstede’s cultural model. A small and medium automotive company in Malaysia, XYZ Automotive was chosen to be the focus of this study. Survey has been used to collect the data via questionnaire, interview and observation. Commitment from employees and top management is crucial for sustainable manufacturing success as explained by Hofstede’s collectivism and power distance dimension. Collectivism and high power distance dimensions work hand in hand in determining the success of sustainable manufacturing practices in XYZ Automotive.